Cave Stedocys spitting spiders illuminate the history of the Himalayas and southeast Asia. Issue 2 (4th April 2017) - Luo, Yufa; Li, Shuqiang
Abstract : Stedocys spitting spiders (Araneae: Scytodidae) inhabit subterranean environments and have poor dispersal abilities. The Cenozoic Indian–Eurasian collision affected the regional biota of this genus, which occurs in parts of Indochina. Phylogeographical pattern of Stedocys based on multigene DNA sequence datasets reveals how tectonic history drove four biological splits. The first split dates to the late Paleocene–Eocene and involves the Truong Son Mountain Range and Mekong River. The other splits associate with the Eocene–Oligocene transition, including the Tonkin (Beibu) Gulf, the Ma River, and the Red River. These events indicate four early uplifts of the Himalayas and Tibetan Plateau. Our results cannot reject the hypothesis that uplifting of the Himalayas and Tibetan Plateau region due to crustal thickening and the lateral extrusion of Indochina occurred synchronously during the Paleocene–Oligocene transition in reaction to the Indian–Eurasian collision. Species of Stedocys cluster into groups I and II. Their evolution involves one dispersal and four vicariance events, which formed the following five Indochinese clades: Hainan clade (I‐1); western Yunnan and central Laos clade (I‐2); central Vietnam clade (I‐3); northern Vietnam and southwestern China clade (I‐4); and Thailand clade (II‐1). The lateral extrusion of Indochina is the driver of these events. The drifting of Hainan Island to its present location owes to its southeastern movement from continental Vietnam and Guangxi, China around the Eocene–Oligocene boundary. This biogeographical pattern highlights the significant role geography plays in shaping evolutionary history in southeastern Asia. It also illuminates how the timing of geological events drives the distributions of species.